On the Matter and Intelligence of the Architectural Model: Arthur Schopenhauer's Psychophysiological Theory of Architecture and Konrad Wachsmann's Design of a Space Structure. Issue 1 (4th January 2017) - Watson, Victoria
During the last decades of the twentieth century, the modernist concept of 'space' in architecture became a subject of inquiry for architectural critics and historians. One curiosity arising within the discourse suggested that the thinking of the nineteenth-century philosopher Arthur Schopenhauer was foundational for the concept of 'space' that developed in German aesthetics throughout the nineteenth and into the twentieth centuries, eventually informing modernist architectural theory. This essay looks at the way Schopenhauer used architectural models, not only to clarify his understanding of space, but also to demonstrate what was for him the much more important notion of 'Idea'. It then turns to the German modernist architect Konrad Wachsmann, who was most famous for his seminal book, The Turning Point of Building (1961), which advocated the industrialization of building as a project for architecture. The essay asks if Schopenhauer's distinction between 'space' and 'Idea' can illuminate the new 'understanding of space' that Wachsmann thought would arise as a consequence of a systematic industrialization of building. Discussion will focus on a particular section of Wachsmann's book that gives an account of his design of a space structure commissioned by the US Air Force in 1959, taking that project as exemplary of his thinking, working methods and values. It will also take note of the way in which the space structure stimulated the imagination of the American artist, Robert Smithson, who began to envisage the entire planet as encapsulated in an enormous virtual grid – one that was, like a Schopenhauerian 'Idea', supposedly constituted out of mind and matter. To end the essay looks briefly at the notion of 'field, ' which, many architects argued at the time, would supersede 'space' as the conceptual mainspring of theory and practice.